A comparative study between kessler suture versus polypropylene mesh implantation to repair tenotomized common calcaneal tendon in rabbits - Saddam Humadi (Iraqi Journal of Veterinary Sciences, 2019)
The present study is assigned to throw the light on the benefit of using Kessler suture compared with polypropylene mesh implantation in healing of induced tenotomy of common calcaneal tendon in a rabbit model based on clinico-histopathological evaluation. Twenty adults New Zealand white male rabbits were used for this clinical prospective study divided equally and randomly into two groups. The first group, (suture group n=10) and the second group (mesh group n=10). Under the effect of general anesthesia, longitudinal skin incision over the common calcaneal tendon was made, and the skin flap was reflected. The tendon was isolated by blunt dissection from the surrounding tissue, with small curved forceps. Simulation of a rabbit’s common calcaneal tendon rupture was made by sharp transvers incision with scalpel. The first group repair with (Kessler Suture) using polypropylene suture size 4.0. In contrast, the second group repair with (polypropylene mesh implantation) after initial suturing of the cut ends of tendon by two simple interrupted stitches using polyglyconate suture size 4.0. The surgical skin wounds were re-stitched by simple interrupted pattern with 3-0 silk. After clinical follow-up of the treatment rabbits, certain secondary health problems were encountered represented by swelling of operative site and lameness. Grossly, adhesions were noticed between the tendon and subcutaneous tissue in rabbits of both groups. Microscopical examination reflected presence of inflammatory cells perivascular edema and few capillaries at two months. At the end of experiment there were perfect orientation and organization of collagen fibers in mesh group in comparing with suture group. Based on the results obtain from this study, it seemed that both groups reflected best outcome in healing of operated tendons with superiority of mesh group in comparing with suture group.